2012
DOI: 10.1021/nn303472r
|View full text |Cite
|
Sign up to set email alerts
|

Cationic PAMAM Dendrimers Aggressively Initiate Blood Clot Formation

Abstract: Poly(amidoamine) (PAMAM) dendrimers are increasingly studied as model nanoparticles for a variety of biomedical applications, notably in systemic administrations. However, with respect to blood contacting applications, amine-terminated dendrimers have recently been shown to activate platelets and cause a fatal, disseminated intravascular coagulation (DIC)-like condition in mice and rats. We here demonstrate that, upon addition to blood, cationic G7 PAMAM dendrimers induce fibrinogen aggregation, which may cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
148
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(162 citation statements)
references
References 42 publications
12
148
0
2
Order By: Relevance
“…Finally, Jones et al (2012) demonstrated that G7 PAMAM dendrimers, with amine terminal groups, induce fibrinogen aggregation after injection in zebrafish larvae of 96 hpf, which may contribute to a disseminated intravascular coagulationlike phenomenon. In this way, once again, the results obtained by these authors emphasize the importance of studying nonlethal side effects of positively charged dendrimers.…”
Section: Dendrimersmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, Jones et al (2012) demonstrated that G7 PAMAM dendrimers, with amine terminal groups, induce fibrinogen aggregation after injection in zebrafish larvae of 96 hpf, which may contribute to a disseminated intravascular coagulationlike phenomenon. In this way, once again, the results obtained by these authors emphasize the importance of studying nonlethal side effects of positively charged dendrimers.…”
Section: Dendrimersmentioning
confidence: 98%
“…To our knowledge, only four publications describe the use of the zebrafish model to analyze the toxicity of diverse dendrimer types (Bodewein et al 2016;Heiden et al 2007;Oliveira et al 2014;Pryor et al 2014) (Table 3). Another two papers have used the zebrafish model to test the toxicity of drug-dendrimer complexes (Prieto et al , 2014; and another one to test the biocompatibility of dendrimers with zebrafish red blood cells (Jones et al 2012). Heiden et al (2007) exposed zebrafish embryos of 6 h post-fertilization (hpf) to G3.5 and G4 PAMAM dendrimers and found that G4 PAMAM dendrimers, with amine terminal groups, were toxic in lethal and sublethal parameters in a dose-and time-dependent way, and that G3.5 PAMAM dendrimers, with carboxylic terminal groups, were not toxic at any of the concentrations tested (no increase in mortality and no sublethal signs of toxicity or malformations).…”
Section: Dendrimersmentioning
confidence: 99%
“…9,[20][21][22][23] Recent studies in mice and zebrafish (Danio rerio) have also shown polyamidoamine (PAMAM) dendrimers with amine terminated groups affected blood-clot formation when administered intravenously, while neutral and anionic dendrimers of the same generation demonstrated no observable vascular complications. 24,25 The authors suggest that these effects are driven by the high affinity amine for platelets or vascular endothelium. 24 The observed toxicity with dendrimers however, is likely due to a combination of generation and charge, as the net charge is dependent on the generation.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 The authors suggest that these effects are driven by the high affinity amine for platelets or vascular endothelium. 24 The observed toxicity with dendrimers however, is likely due to a combination of generation and charge, as the net charge is dependent on the generation. 11,18 In contrast with PAMAM dendrimers, the limited research on thiophosphoryl dendrimers has demonstrated minimal inherent toxicity in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced zeta potential in hydrogenated complexes facilitates the interaction between peptide molecules, resulting in conversion of Aβ40 from random coils to β-sheet structures. 79 Very recently, Jones et al 80 demonstrated that fibrinogen, and other anionic blood proteins, undergo rapid and extensive aggregation by densely charged cationic G7 dendrimers through a thrombinindependent and cellular activation-free mechanism. The acidic nature of these proteins and their high concentration in blood predispose these elements to aggregation with oppositely charged dendrimers.…”
mentioning
confidence: 99%